Out of Asia: learning re-examined, teacher education re-configured - Dobinson, Toni (Routledge, 2012)
The impetus for this argumentative paper is anecdotal evidence overheard in West Australian educational settings indicating that there continues to be “othering” of learners from Asian backgrounds. Exploring prevailing Western social, theoretical and educational discourses associated with Asia, the author argues that teacher education in Western Australia be reconceptualized in three main ways. Firstly, levels of meta-cultural sensitivity in pre-service and in-service educators should be ascertained. Secondly, there needs to be a more rigorous theoretical and conceptual framework for pre-service/in-service teacher education informed by cross-cultural, historical knowledge and awareness of the social and personal constructions of reality – views of the “other” and “self”. Thirdly, teacher education courses must offer opportunities to examine current developments in educational research which encourage reconceptualization and replacement of traditional East/West dichotomies. The paper aims to review literature related to theoretical Thirdness as an ontological, educational principle and to contribute to Thirdness discourse by situating the argument in a particular context in Western Australia. It is hoped that papers such as this may lead to more informed and symmetrical dialogue between educators in the Asia Pacific region.